THE CONTRIBUTION OF BIO-POLYMERS TO PHARMACEUTICAL INDUSTRY : EVALUATION OF CELLULOSE PROCESSED FROM THE HOLLOW STEMS AND LEAVES OF COMMON REED, PHARGMETS AUSTRALIS, F. GRAMINACEAE, AS TABLETTING EXCIPIENT - Nayef Saleh Al-muaikel (European Scientific Journal, ESJ, 2012)
The leaves and the hollow stem of Phargmets Australis, a plant growing widely near water sources in Sakaka town, were used as a crude material to extract cellulose 1. Commercial grade of native cellulose was employed as a reference material for the comparative study. The extracted cellulose, PC, was found to comprise of long, fibrous particles of irregular shape and rough surface which creat resistance to flow. The extracted cellulose powder was not freely flowing. The addition of a glidant was found to reduce the inter-particulate friction and induced a positive effect on the flow rate and repose angle of the powder 2 . Beyond 3.5 % w/w, the fine particles of the added glidant furnish inter-particulate bridging and the powder became co-hesive. Moisture sorbed by an added glidant was found to be the affect its glidant action. Magnesium stearate followed by stearic acid and aerosol 200 were at 2% w/w, respectively were the most effective glidants.